2018
DOI: 10.3389/fphys.2018.01576
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Body Electromyostimulation Improves Performance-Related Parameters in Runners

Abstract: The aim of this study was to study the effects of a 6-session (one per week) WB-EMS training intervention on maximum oxygen uptake, aerobic and gas exchange thresholds, running economy, and muscular power in male recreational runners. Twelve men were randomized into WB-EMS intervention (n = 6; 27.0 ± 7.5 years; 70.1 ± 11.1 kg; 1.75 ± 0.5 m) or control (n = 6; 27.0 ± 6.1 years; 73.6 ± 3.4 kg; 1.77 ± 0.3 m). The WB-EMS group reduced the running training frequency to one per week and followed one WB-EMS training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 47 publications
3
33
1
Order By: Relevance
“…Whole‐body electromyostimulation training is able to stimulate all the main muscle groups with dedicated intensity simultaneously and has become increasingly popular during the last decade. A total of 21 studies have investigated its influence on physical fitness and health in trained and untrained individuals, and in patients who cannot perform conventional modalities of exercise because of physical or mental illness . Most of these studies (n = 10) have examined the role of whole‐body electromyostimulation training on body composition parameters, showing that this training modality induced a generally decrease of FM and a generally increase of LM in (a) sedentary older men and women with sarcopenic obesity (all of them aged > 70 years old), (b) in sedentary older women with obesity (aged > 70 years old), (c) in moderately trained male runners, (d) in sedentary healthy men (aged 30‐50 years old), and (e) in moderately trained healthy women (aged > 55 years old) .…”
Section: Introductionmentioning
confidence: 99%
“…Whole‐body electromyostimulation training is able to stimulate all the main muscle groups with dedicated intensity simultaneously and has become increasingly popular during the last decade. A total of 21 studies have investigated its influence on physical fitness and health in trained and untrained individuals, and in patients who cannot perform conventional modalities of exercise because of physical or mental illness . Most of these studies (n = 10) have examined the role of whole‐body electromyostimulation training on body composition parameters, showing that this training modality induced a generally decrease of FM and a generally increase of LM in (a) sedentary older men and women with sarcopenic obesity (all of them aged > 70 years old), (b) in sedentary older women with obesity (aged > 70 years old), (c) in moderately trained male runners, (d) in sedentary healthy men (aged 30‐50 years old), and (e) in moderately trained healthy women (aged > 55 years old) .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the results could be explained by the high overall training status of the subjects. Due to the documented effects of strength training on runner´s performance [37] and effects of EMS application on runner´s VO 2 max [6], we analysed effects on some endurance parameter for EG. Indeed, WB-EMS intervention with dynamic exercises and training status of the subjects (VO 2 max: 53 mL/min/kg) were similar to the study of Amaro-Gahete et al [6].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the documented effects of strength training on runner´s performance [37] and effects of EMS application on runner´s VO 2 max [6], we analysed effects on some endurance parameter for EG. Indeed, WB-EMS intervention with dynamic exercises and training status of the subjects (VO 2 max: 53 mL/min/kg) were similar to the study of Amaro-Gahete et al [6]. However, the differential results might be attributed to differences in current frequency (12-90 vs. 85 Hz), higher time under tension (6 vs. 2 min) and higher intensities of exercises with superimposed EMS (strength and interval exercise vs. jumps) in the cited study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The improvements in cardiovascular system performance found in the present study could be explained from a physiological perspective by Filipovic et al [63], who observed in elite soccer players positive effects of WB-EMS on the deformability of red blood cells, an important factor in the distribution of O2 to muscle tissue. Amaro et al [64] observed a significant increase in VO2max and aerobic and anaerobic thresholds after a 6-week periodized WB-EMS training. Their sample was formed by young athletes, but we consider it interesting to mention the results of this study, taking into account that thresholds are very reliable markers of cardiovascular system health [65].…”
Section: Cardiovascular Endurancementioning
confidence: 97%